PERANAN KOMPETENSI PEGAWAI MEMEDIASI PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP EFEKTIVITAS ORGANISASI - Anggreni, Kadek Ayu; Ardana, I Komang (E-Jurnal Manajemen, 2019)
This study aims to analyze the role of employee competencies to mediate the influence of education and training (diklat) on organizational effectiveness. Samples were taken as many as 80 respondents, namely employees of the Trade and Industry Office of the province of Bali who had attended education and training before while the analysis technique used was Path Analysis. Based on the results of the analysis found that education and training had a positive and significant effect on competence. employees and have a positive and significant effect on organizational effectiveness. Employee competence has a positive and significant effect on organizational effectiveness. The results of this study also prove that employee competence positively and significantly mediates the influence of education and training (diklat) on organizational effectiveness. Theoretical implications of the results of this study clarify the influence of education and training (training) variables on organizational effectiveness mediated by employee competence. This study shows that the role of education and training programs (diklat) will improve organizational effectiveness supported by high employee competencies. Keywords : education, training, competence, organizational effectiveness